An experimental design approach to manufacture of parts using fused deposition modelling. (20th October 2010) - Sendilkumar, M.; Prasad, P.S.S.
Investigating the mechanical properties of the parts manufactured from rapid prototyping (RP) machine is important for rapid manufacturing. It is necessary that, the identification of effect of different combination of process parameters to get the desired mechanical properties. This paper presents a method to manufacture parts with different combination of process parameters of fused deposition modelling (FDM) using design of experiments. The effect of road width (RW) and raster angle (RA) on density, hardness, and surface roughness is investigated. The experiments have been conducted based on second order central composite rotatable design which is one type of response surface methodology. The 13 samples are prepared and tested. From the results, the regression coefficients are calculated and fitted to the general form of quadratic equation for two factors. By using statistical analysis, the significance of the various factors is determined. The final relation shows the effect of input parameters over the output response.